The Effectiveness of Tzuyu as a Brand Ambassador in launching Pond’s Bright Miracle Products on @pondsindonesia Followers - Rachel Ade Suryaning Kalla; Inri Inggrit Indrayani; Daniel Budiana (Petra Christian University, 2024)
This study aims to measure the effectiveness of Tzuyu as a brand ambassador in launching Pond's bright miracle products on the @pondsindonesia Instagram account. A brand ambassador is someone who is the representative or face of a brand used by companies to communicate and connect with the public. The use of popular celebrities as brand ambassadors in product launches will attract greater attention. Tzuyu is a member of one of the famous girl groups in South Korea, Twice. Pond's appointed Tzuyu as a brand ambassador in the launch of Pond's bright miracle product by using Instagram social media as a tool to convey messages to the audience. This study measures the effectiveness of a brand ambassador using the theory of source credibility by Ohanian (1990). This research uses a descriptive quantitative approach with data collection techniques using an online questionnaire via google form. The purposive sampling technique is in accordance with the criteria determined in selecting respondents who fill out the questionnaire. The results showed that Tzuyu as Pond's brand ambassador in the launch of Pond's bright miracle was declared effective, with attractiveness being the most effective indicator.